Numerical Solution of Unsteady Hydromagnetic Natural Convection Flow of Heat Absorbing Fluid past an Impulsively Moving Vertical Plate with Ramped Temperature - Seth, Gauri Shanker; Sarkar, Subharthi; Mahato, Goutam Kumar (International Journal of Applied Mathematical Research, 2013)
A numerical investigation of unsteady hydromagnetic natural convection flow of a viscous, incompressible, electrically conducting and heat absorbing fluid past an impulsively moving vertical plate with ramped temperature embedded a porous medium in the presence of thermal diffusion is carried out. The governing equations are solved numerically by Crank-Nicolson implicit finite difference scheme. The numerical solution for fluid velocity and fluid temperature are depicted graphically whereas the numerical values of skin friction and Nusselt number are presented in tabular form for various values of pertinent flow parameters. Natural convection flow near a ramped temperature plate is also compared with the flow near an isothermal plate.